Riscos e complicações associadas à Infecção do Sitio Cirúrgico : um estudo de coorte - Carvalho, Thialla Andrade (2016)
Purpose: to identify the occurrence of cross infection, the associated risks and its correlation with hospital stay and mortality in patients attended at a teaching hospital located in the northeastern region of Brazil. Methods: prospective cohort study, with information collected in medical records and kept on adverse event surveillance forms during the year 2015. The data were entered and analyzed in Epi-Info7 software. The variables studied were related to patients, procedures and outcomes. Results: A total of 752 adverse events surveillance forms were evaluated, with an overall incidence of 4,52% for Surgical Site Infection (SSI). A statistically significant association was found in the univariate analysis of SSI and the variables studied: contaminated surgeries, surgeries without laparoscopic techniques, patients with severe systemic alteration, patients with functional limitation, Nosocomial Infections Surveillance (NNIS) Risk Index (IRIC) ≥1 and in procedures that did not use Microbial prophylaxis in accordance to standardized Hospital Infection Control Service (HICS). The independent association with SSI was observed for NNIS and non-specified intra-abdominal surgery elsewhere. It was also demonstrated a significant association between the diagnosis of SSI and increased mortality and hospital stay.Conclusion: This study demonstrates the significant impact of risk factors for the occurrence of SSI and allows the establishment of strategies that improve the quality of patient care and safety.